ASSESSMENT OF EFFICIENCY OF USE OF A NEW WAY OF TREATMENT OF CHRONIC ANAL CRACKS - E. A. Rogozhkina; V. S. Groshilin; V. G. Zaika (Медицинский вестник Юга России, 2013)
Purpose: Assessment of results of surgical treatment of patients with chronic anal cracks with violations of the psychoemotional sphere in the form of alarm and a depression, revealed by means of a hospital scale of alarm and HADS depression.Materials and methods: The hospital scale of HADS in the preoperative and postoperative period was used, the locking device of a rectum in the preoperative period for definition of a quantitative assessment of expressiveness sphincter spasm was investigated. In work results of surgical treatment of 98 patients were analyzed.Results: Psychopharmacotherapy application in the postoperative period for the purpose of correction of disturbing and depressive violations is recommended.Summary: The offered way of treatment of a chronic anal crack taking into account changes of the psychoemotional status and their correction in a complex with surgical and conservative treatment in the postoperative period leads to improvement of subjective health of patients, allows to influence results of surgical treatment, reducing terms of healing of a postoperative wound, reducing risk of emergence of recurrence of surgical treatment of such patients.